Global applications of the frailty index based on the deficit accumulation model - Xuemei Cai; Xiaodong Yao (Guoji laonian yixue zazhi)
Frailty is a prevalent geriatric syndrome associated with adverse health outcomes among the elderly. Currently, there is no uniform standardized tool for frailty assessment.The frailty index (FI), based on the concept of deficit accumulation, evaluates a broader range of health information and is recognized for its superior accuracy in predicting adverse clinical outcomes, such as mortality, hospital readmissions, and disability.This review focuses on the FI derivatives models, its application in various contexts, and its comparison with other assessment tools.The aim is to provide insights for utilizing the FI to better identify high-risk groups that are more susceptible to debilitating conditions.